Intrinsic properties of anodic TiO2 nanotube layers: In-situ XRD annealing of TiO2 nanotube layers - Sopha, Hanna Ingrid; Spotz, Zdenek; Sepulveda Sepulveda, Lina Marcela; Alijani, Mahnaz; Motola, Martin; Hromádko, Luděk; Macák, Jan (Elsevier Science, 2023)
In this work, in-situ annealing of TiO2 nanotube (TNT) layers in an XRD chamber was carried out to investigate the crystallization process of the TNT layers in details. TNT layers of different thicknesses, i.e. 1, 5 and 20 & mu;m, and of different morphology, i.e. double wall vs. single wall, were annealed in the temperature range from room temperature to 500 degrees C with two distinctly different annealing rates. Additionally, three different annealing atmospheres were explored, namely air as an oxidative, N2 as an inert, and 5%H2/95%N2 as a reductive atmosphere. XRD patterns were measured every 15 degrees C of the heating ramp and the crystallite sizes of anatase phase were calculated from the anatase peak using Scherer equation at each data point. The differences in crystallization behavior for the different TNT layers as well as the effect of the annealing atmosphere for 5 & mu;m thick TNT layers are described and discussed.
Vnitřní vlastnosti anodických vrstev nanotrubiček TiO2: In-situ XRD žíhání vrstev nanotrubiček TiO2
Keywords: TiO 2 nanotube layers; In -situ XRD; Annealing; Crystallization; vrstvy nanotrubiček Ti02; XRD in situ; Žíhání; Krystalizace